Synergistic activity of several acids in binary mixtures with synthetic insecticides on Spodoptera littoralis (Boisduval) - Hatem, A.E.=700 1 Homam, H.B.; Amer, R.A.; Abdel-Samad, S.S.M.; Saleh, H.A.; Huáien, A.I.
(Es, En)
Ilus., 34 ref.
Keywords: SPODOPTERA LITTORALIS; CONTROL BIOLOGICO; ACIDOS INORGANICOS; ACIDOS ORGANICOS; ESPAÑA; BOLETIN DE SANIDAD VEGETAL: PLAGAS